Because of Winn-Dixie - DiCamillo, Kate. (Cambridge, Mass. : Candlewick Press, 2000)
Ten-year-old India Opal Buloni describes her first summer in the town of Naomi, Florida, and all the good things that happen to her because of her big ugly dog Winn-Dixie.
Keywords: Dogs -- Fiction; City and town life -- Florida -- Fiction; Florida -- Fiction